Peran Manajemen Pendidikan dalam Mewujudkan Pendidikan Berkualitas - Prabuyanti, Dwi (Yayasan Sembilan Pemuda Indonesia, 2025)
Educational management has a very important role in realizing quality education, which aims to improve the quality, effectiveness, and efficiency of the education process. The purpose of this study is to examine more deeply the role of educational management in realizing quality education. The research method that will be used in this study is a literature study approach, where data and information will be collected from various academic sources, such as books, journals, and relevant articles on educational management and realizing quality education. The results of this study indicate that quality management plays a key role in creating quality education through main components such as curriculum, human resources, financial management, facilities and infrastructure, and cooperation with external parties. Each of these components works synergistically to support an optimal learning process, although it often faces challenges, such as limited resources, resistance to change, and lack of stakeholder support. Through collaboration from various parties, including the government, community, and parents, schools can overcome these challenges. The role of educational management equipped with Educational Quality helps improve the professional quality of teachers, curriculum, and school management, as well as build cooperation with external parties. This synergy produces schools that are quality, adaptive, and able to answer the demands of today's education.